Evaluation of pharmacokinetic, pharmacodynamic, efficacy, and safety data of low-dose ticagrelor versus standard dose in East Asians: a systematic review - Lee YJ; Kim HW; Choi JY; Lee BH; Lee SY (Therapeutics and Clinical Risk Management, 2018)
Yun Jeong Lee,1 Hyewon Kim,1 Jiyeon Choi,1 Bo Hee Lee,1 Seok-Yong Lee2 1Department of Pharmacy, College of Pharmacy, Dankook University, Cheonan, Republic of Korea; 2Department of Pharmacy, School of Pharmacy, Sungkyunkwan University, Suwon, Republic of Korea Abstract: East Asians are prone to higher systemic exposure and increased risk of bleeding compared to other races after administration of antiplatelet agent(s). The aim of this systematic review was to compare and evaluate the appropriateness of a lower dose versus standard dose of ticagrelor in East Asians. A systematic search was conducted in PubMed, EMBASE, and Cochrane databases for studies comparing low versus standard doses of ticagrelor in East Asian populations; a total of seven studies were included in the review. Pharmacokinetic (PK), pharmacodynamic (PD), clinical efficacy, and safety data were collected. PK data demonstrated that the Cmax and area under the curve (AUC) of ticagrelor increased dose-proportionally. PD data indicated that while the low dose of ticagrelor resulted in less antiplatelet activity in three of the five PD studies, in the other studies, there were no differences between low and standard doses. There were two clinical studies included in this review, which showed that the efficacy was similar between the low and standard doses, but both studies were limited by the number of patients included. While there were generally greater incidence of adverse events observed in the standard ticagrelor dose, the magnitude or actual difference between the two doses is difficult to determine due to lack of consistent data. In East Asians, the appropriateness of the low-dose ticagrelor cannot be determined based on the currently available evidence. Additional large-scale and longer duration studies are warranted. Keywords: ticagrelor, P2Y12 receptor antagonist, lower dose, East Asians, Korean, Japanese, Chinese, efficacy, safety